Educação ambiental e formação de professores: o caso dos cursos de licenciatura nas universidades públicas do Estado do Amazonas, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Article 11 of Law 9795/99, which deals with the National Environmental Education Policy in Brazil, states that Environmental Education must be included in teacher training courses. The dissertation is entitled: Environmental Education and Teacher Training: the case of undergraduate courses at public universities in the state of Amazonas, Brazil. Its main objective was to analyze scientific productions published in the period from 1997 to 2022. The study sites were the Federal and State Universities of the state of Amazonas. The methodology was based on the quantitative/qualitative approach, through scientometrics and the instruments were the CAPES and Web of Science Platforms. To interpret the data, the content analysis technique was used, and the data was searched using Boolean operators. The results achieved were: a) 1442 scientific productions were found on the CAPES platforms, while 302 productions were found on the WEB OF SCIENCE; b) On the CAPES platform, there was a highlight of productions in the years 2016, 2018, 2020, 2021 and a greater incidence in 2022. On the other hand, on the Web of Science platform there was a highlight of productions published in 2015 and a greater incidence in the year 2022; c) in 2018, research was highlighted on environmental issues in non-formal spaces, competence in teacher training (LDB/BNC), the fight for teacher training, among others. Environmental Education is an instrument capable of helping human beings in the search for environmental sensitivity and awareness, and in teacher training courses, whether in the state of Amazonas or in any reality on the planet, it must be worked in a participatory, interdisciplinary, routine manner in search for a quality environment.
Keywords: Educação Ambiental; Formação de Professores; Universidades Públicas Federais e Estaduais; Amazonas (Estado); Cienciometria; CNPQ::CIÊNCIAS SOCIAIS APLICADAS